-30+7z=-5(3z+9)

Simple and best practice solution for -30+7z=-5(3z+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -30+7z=-5(3z+9) equation:


Simplifying
-30 + 7z = -5(3z + 9)

Reorder the terms:
-30 + 7z = -5(9 + 3z)
-30 + 7z = (9 * -5 + 3z * -5)
-30 + 7z = (-45 + -15z)

Solving
-30 + 7z = -45 + -15z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '15z' to each side of the equation.
-30 + 7z + 15z = -45 + -15z + 15z

Combine like terms: 7z + 15z = 22z
-30 + 22z = -45 + -15z + 15z

Combine like terms: -15z + 15z = 0
-30 + 22z = -45 + 0
-30 + 22z = -45

Add '30' to each side of the equation.
-30 + 30 + 22z = -45 + 30

Combine like terms: -30 + 30 = 0
0 + 22z = -45 + 30
22z = -45 + 30

Combine like terms: -45 + 30 = -15
22z = -15

Divide each side by '22'.
z = -0.6818181818

Simplifying
z = -0.6818181818

See similar equations:

| 7/3x=-6/7 | | 6x+28=x+8 | | -4(6y+4)+19=12(-2y+5)-55 | | 5y-9y+6x-2x= | | 2(3)+y=72 | | x/(x-3)-4=3/(x-3) | | 2z=1.7+0.9 | | -11x+31-8x+40x-9=-5x+8+15x | | 5x-16+7=x+4+7 | | 3(5x+8)=-10+19 | | 2(0)+y=72 | | 4(5x+4)=-56 | | 35=12y-8y | | 4.2u-5-6.5u= | | -5(n+2)+13=-2n-15 | | 40=4y-16 | | 5x-4+5x-4+2x+3=187 | | 9x-12=-20 | | 8(3v+4)=22-9v | | 3t-3t=-9+9t | | 2(-4z-5)+16=-2(4z-3)+0 | | 17x-4(x-2)=-5 | | 5x-2+10=4x+8+10 | | 3.50=1.90+c | | -24x-31-8x+40x-9=-5x+8+15x | | Inx=-In(x+1) | | 2(3x-1)=x^2+7x-8 | | 26+4y-8=14y-10-3y | | 40*x+(12.5x*1.5)= | | 3.5h=14 | | 2.25(x-42)=x+3.28 | | 2=y/3.2 |

Equations solver categories